Graphene Oxide-Based Membranes for Water Purification Applications: Effect of Plasma Treatment on the Adhesion and Stability of the Synthesized Membranes - Omer Alnoor; Tahar Laoui; Ahmed Ibrahim; Feras Kafiah; Ghaith Nadhreen; Sultan Akhtar; Zafarullah Khan (Membranes, 2020)
The adhesion enhancement of graphene oxide (GO) and reduced graphene oxide (rGO) layer in the underlying polyethersulfone (PES) microfiltration membrane is a crucial step towards developing a high-performance membrane for water purification applications. In the present study, we modified the surface of a PES microfiltration membrane with plasma treatment (PT) carried out at different times (2, 10, and 20 min). We studied the effect of PT on the adhesion, stability, and performance of the synthesized GO/rGO-PES membranes. The membranes’ surface morphology and chemistry were characterized using atomic force microscopy, field emission scanning electron microscopy, and Fourier transform infrared spectroscopy. The membrane performance was evaluated by conducting a diffusion test for potassium chloride (KCl) ions through the synthesized membranes. The results revealed that the 2 min PT enhanced the adhesion and stability of the deposited GO/rGO layer when compared to the other plasma-treated membranes. This was associated with an increase in the KCl ion rejection from ~27% to 57%. Surface morphology analysis at a high magnification was performed for the synthesized membranes before and after the diffusion test. Although the membrane’s rejection was improved, the analysis revealed that the GO layers suffered from micro/nano cracks, which negatively affected the membrane’s overall performance. The use of the rGO layer, however, helped in minimizing the GO cracks and enhanced the KCl ion rejection to approximately 94%. Upon increasing the number of rGO deposition cycles from three to five, the performance of the developed rGO-PES membrane was further improved, as confirmed by the increase in its ion rejection to ~99%.